2010
DOI: 10.1177/0047287510362781
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficacy of an Integrative Model for Community Participation

Abstract: The purpose of this study was to examine the efficacy of an integrative model for community participation in tourism development. Termed as motivation—opportunity—ability (MOA), the model integrated two streams of research, “means” and “ends” oriented studies, with the intent of providing a holistic view of community participation research. To test the hypothesized relationships, data were collected from a stratified random sample of households in Charleston, South Carolina. The data provided some support for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 49 publications
3
144
2
3
Order By: Relevance
“…Furthermore, a person's level of education directly influences his/her socio-economic opportunities and outcomes through employment, in this case employment in the tourism sector. Hung, K. et al [47] observed that ability to participate in tourism activities depends on various factors including knowledge, skills and financial resources. Furthermore, education brings significant benefits to individuals and society through exposure to and knowledge of business opportunities, income, enhanced skills, improved social status and access to networks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a person's level of education directly influences his/her socio-economic opportunities and outcomes through employment, in this case employment in the tourism sector. Hung, K. et al [47] observed that ability to participate in tourism activities depends on various factors including knowledge, skills and financial resources. Furthermore, education brings significant benefits to individuals and society through exposure to and knowledge of business opportunities, income, enhanced skills, improved social status and access to networks.…”
Section: Discussionmentioning
confidence: 99%
“…Within the CBT literature, the need for community participation to mitigate conflict 'instances' has been quite prolific (Hung et al, 2011;Murphy & Murphy, 2004;Reed, 1997;Reid et al, 2004;R. Scheyvens, 2002;Simpson, 2008;Yang et al, 2013).…”
Section: Participationmentioning
confidence: 99%
“…As a result of empowerment through participation and an increase in capacity, some of the literature has discussed community members experiencing an increase in motivation (Hung et al, 2011;Stronza & Gordillo, 2008).…”
Section: Empowermentmentioning
confidence: 99%
“…La toma de conciencia de la existencia de estas percepciones negativas relacionadas con el desarrollo del turismo en una comunidad ha fomentado el énfasis en la noción de desarrollo turístico sostenible, reclamando la participación de los residentes en el proceso de desarrollo turístico (Hung, Sirakaya & Ingram, 2011). De esta manera, el grado en que se satisfacen los deseos de los residentes y su punto de vista es tomado en consideración, determina su receptividad tanto al desarrollo turístico como a los propios turistas (Davis, Allen & Cosenza, 1988).…”
Section: Marco Teóricounclassified
“…En este sentido, los residentes deben ser un punto de atención esencial en el proceso de toma de decisiones (Choi & Sirakaya, 2005) y se debe reconocer, por tanto, a la comunidad local como una parte integral del turismo sostenible (Hung, Sirakaya & Ingram, 2011).…”
Section: Marco Teóricounclassified